2021
DOI: 10.3389/fbioe.2021.633468
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles by Aspergillus terreus: Characterization, Optimization, and Biological Activities

Abstract: In this study, mycelial filtrate of Aspergillus terreus BA6 was used to reduce AgNO3 to form silver nanoparticles (AgNPs). The effect of seven independent variables on the diameter of AgNPs was studied by applying design of experiments (DOE). At optimal conditions, the diameter of AgNPs was reduced by approximately 26.7% compared to the basal culture condition and AgNO3 concentration was found to be the most significant factor affecting the diameter of AgNPs. A. terreus nano-Ag was characterized using UV-visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 57 publications
(73 reference statements)
6
35
0
1
Order By: Relevance
“…106 The noted activity of all fungal-based NPs against K. pneumoniae might be due to the structure of cell wall of Gram-negative bacteria. 107 Regarding MIC and MBC, a recent study by Lotfy et al 94 reported a similar kind of observations when they studied NPs mediated by Aspergillus terreus against twelve bacteria, where P. aeruginosa and S. faecalis showed the highest susceptibility. Similar research by Sathiyaraj et al 92 revealed that AgNPs prepared by Vallarai chooranam showed a high zone of inhibition against E. coli and low one against Bacillus subtilis.…”
Section: Antibacterial Activity Of Agnpsmentioning
confidence: 61%
See 2 more Smart Citations
“…106 The noted activity of all fungal-based NPs against K. pneumoniae might be due to the structure of cell wall of Gram-negative bacteria. 107 Regarding MIC and MBC, a recent study by Lotfy et al 94 reported a similar kind of observations when they studied NPs mediated by Aspergillus terreus against twelve bacteria, where P. aeruginosa and S. faecalis showed the highest susceptibility. Similar research by Sathiyaraj et al 92 revealed that AgNPs prepared by Vallarai chooranam showed a high zone of inhibition against E. coli and low one against Bacillus subtilis.…”
Section: Antibacterial Activity Of Agnpsmentioning
confidence: 61%
“… 87 The peaks at 3.0 keV in the EDX spectrum represented Ag attributed to the SPR of Ag nanocrystals as reported earlier. 92 , 94 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of aqueous extract and green synthesized SNPs were tested on the Vero cells by MNTC method of each extract that determined in the range of the cytotoxic concentrations at 0-600 µg mL −1 for aqueous extract, and 0-200 µg mL −1 for SNPs pre-and postinfection treatment using 10 4.8 and 10 3.7 TCID 50 mL −1 for IBV and ILTV viruses, respectively. Microscopically demonstrated normal cell morphology was observed and no cytotoxic effect of the extracts on the Vero cells in the range of the cytotoxic concentrations at 0-400 µg mL −1 of aqueous extract, and 0-50 µg mL −1 for SNPs (Table 2) [45,46].…”
Section: Cytotoxicity Effectmentioning
confidence: 97%
“…Silver nitrate is a well-known antimicrobial agent used in the treatment of chronic wounds and for many other medical purposes since ancient times (Paladini and Pollini, 2019 ; Talapko et al, 2020 ; Chinnasamy et al, 2021 ). Silver NPs (AgNPs) show a potent activity against a broad range of Gram-negative and Gram-positive, aerobic and anaerobic bacteria, filamentous fungi, yeast, and viruses (Gaikwad et al, 2013a ; Dakal et al, 2016 ; Alavi and Rai, 2021 ; Lotfy et al, 2021 ; Zawadzka et al, 2021 ; Alavi et al, 2022 ). In the beginning of the twentieth century, morbidity, and mortality were major consequences of burn wound infections (Norbury et al, 2016 ; Ladhani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%